Impact of the Diabetes Inpatient Care and Education (DICE) project on length of stay and mortality. Issue 2 (2nd August 2019) - Akiboye, F.; Adderley, N. J.; Martin, J.; Gokhale, K.; Rudge, G. M.; Marshall, T. P.; Rajendran, R.; Nirantharakumar, K.; Rayman, G.; ,
Abstract: Aim: To determine whether the Diabetes Inpatient Care and Education (DICE) programme, a whole‐systems approach to managing inpatient diabetes, reduces length of stay, in‐hospital mortality and readmissions. Research design and methods: Diabetes Inpatient Care and Education initiatives included identification of all diabetes admissions, a novel DICE care‐pathway, an online system for prioritizing referrals, use of web‐linked glucose meters, an enhanced diabetes team, and novel diabetes training for doctors. Patient administration system data were extracted for people admitted to Ipswich Hospital from January 2008 to June 2016. Logistic regression was used to compare binary outcomes (mortality, 30‐day readmissions) 6 months before and after the intervention; generalized estimating equations were used to compare lengths of stay. Interrupted time series analysis was performed over the full 7.5‐year period to account for secular trends. Results: Before‐and‐after analysis revealed a significant reduction in lengths of stay for people with and without diabetes: relative ratios 0.89 (95% CI 0.83, 0.97) and 0.93 (95% CI 0.90, 0.96), respectively; however, in interrupted time series analysis the change in long‐term trend for length of stay following the intervention was significant only for people with diabetes ( P =0.017 vs P =0.48). Odds ratios for mortality were 0.63 (0.48, 0.82) and 0.81 (0.70, 0.93) in people with and without diabetes, respectively; however, the change in trend was not significant in people with diabetes, while there was an apparent increase in those without diabetes. There was no significant change in 30‐day readmissions, but interrupted time series analysis showed a rising trend in both groups. Conclusion: The DICE programme was associated with a shorter length of stay in inpatients with diabetes beyond that observed in people without diabetes. What's new?: People hospitalized with diabetes have poorer outcomes and longer length of stay than those without diabetes. We report the impact of a multifaceted, whole‐systems approach to diabetes care. Interrupted time series analysis was used to supplement the commonly used before‐and‐after analysis, highlighting the strength of this quasi‐experimental methodology. Our data show that a nurse‐delivered care programme can produce sustained and ongoing reductions in length of stay for people with diabetes in the National Health Service today.